Integrasi Layanan Trans Koetaradja dengan Feeder Angkutan Labi-Labi di Kota Banda Aceh - Afriza, Winiko; Manullang, Okto Risdianto (Universitas Diponegoro, Indonesia, 2020)
The Aceh Provincial Government through the department of transportation in 2016 began operating Bus Rapid Transit (BRT) in Banda Aceh city. The presence of Trans Koetaradja is expected to be able to implement a mass transit system that is capable of maintaining order, traffic congestion and traffic jam in Banda Aceh City. However, the existence of BRT Trans Koetaradja poses a threat to the existence of drivers and businessmen of transporting labi-labi in Banda Aceh City. Starting from the problem, this research aims to create the form of integration of BRT Trans Koetaradja service with feeder of labi-labi transportation in Banda Aceh City. The research method used is descriptive analysis of kunatitatif which will describe the potential of travel demand and condition of existing road network. In addition, it uses a spatial descriptive analysis method to formulate the form of feeder transport routes of labi-labi and analyze the operational integration of routes, time and rates. The result of the research shows that there are 6 feeder routes that will serve the corridor I Keudah-Darussalam namely Prada area route, Zainal Abidin General Hospital route, Simpang Keramat route, Unsyiah campus route and UIN Ar-Raniry route, Aceh Governor Office and route of Simpang Mesra area. Operationally, the integration of Trans Koetaradja transport service time with feeder transport of labi-labi is at 07.00-18.00 wib. The required headway of each feeding route is 4-9 minutes. The travel time required for each feeder route is 10-15 minutes with the number of fleets used by 32 units to serve 6 (six) feeder routes. In terms of tariff integration, the cost to be spent per passenger to use labi-labi transportation on each feeder route is between Rp.1.000 - Rp. 1,500.